How the LiveWell Dorset lifestyle behaviour change service influences older adults' physical activity behaviour: A generic qualitative study - Andrew J. Powell; Sarah Thomas (Elsevier, 2021)
Objectives: There is uncertainty around the most effective characteristics and components of interventions to increase older adults' physical activity (PA) levels. This study aimed to explore how LiveWell Dorset (LWD), a lifestyle behaviour change support service based in Dorset, South-West England, influences older adults' PA behaviour. Study design: A qualitative study using a generic approach. Methods: Semi-structured telephone interviews were held with 12 individuals aged 55 to 65 who had accessed LWD's support to increase their PA levels, to gather their views and experiences of the service. A thematic analysis of the interview data was conducted using a hybrid approach that incorporated both inductive and deductive processes. Additionally, interview content was coded for behaviour change techniques using the Behaviour Change Technique Taxonomy version 1. Results: A number of key factors were identified that highlighted how the LWD service influences older adults' PA behaviour. These included using a broad range of promotional and behaviour change strategies to facilitate initial engagement, providing opportunities for service users to receive social support from both professionals and peers, and emphasising person-centredness and empathy in interactions with service users. Conclusions: The findings provide valuable information regarding the needs and preferences of older adults when attempting to influence their PA behaviour, and on the reportedly helpful components of interventions that aim to do so. The findings also support the need for future research into previously highlighted topics of interest such as the roles of systemic and contextual factors and professional empathy on PA intervention engagement and outcomes.